2021
DOI: 10.1063/5.0056254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phonon modes in 2H-TaX2 (X = S/Se) flakes with electrostatic doping

Abstract: Electrostatic doping-assisted phonon softening has been intensively investigated in semiconducting transition metal dichalcogenides (TMDCs), in which strong electron–phonon interactions can be achieved in thin layers. Though electron–phonon coupling plays an important role in structure phase transitions for metallic 2H-TaX2 (X = S, Se), it has been rarely studied under electrostatic doping. Here, the effect of electrostatic doping on the vibrational phonon modes of 2H-TaSe2 and 2H-TaS2 thin films is studied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…These data demonstrate that chemical intercalation is a viable method for accessing Fe x TaS 2 in the few-layer limit with the potential to vary the stoichiometry and homogeneity. We find that all Raman spectra in Figure e–g display a red shift in the A 1g mode by 8–10 cm –1 from the expected value for 2 H -TaS 2 . , This shift is consistent with electron transfer from Fe to the host lattice, , in agreement with our DFT calculations. For all calculated structures and magnetic configurations, we found that Fe converges to a +2 oxidation state, matching our electron energy loss spectroscopy results (Figure S12) and published experimental data on bulk Fe x TaS 2 . We note that without annealing these chemically intercalated materials, we observe neither superlattice spots in NBED data nor significant changes to the Raman spectra (Figure S5).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These data demonstrate that chemical intercalation is a viable method for accessing Fe x TaS 2 in the few-layer limit with the potential to vary the stoichiometry and homogeneity. We find that all Raman spectra in Figure e–g display a red shift in the A 1g mode by 8–10 cm –1 from the expected value for 2 H -TaS 2 . , This shift is consistent with electron transfer from Fe to the host lattice, , in agreement with our DFT calculations. For all calculated structures and magnetic configurations, we found that Fe converges to a +2 oxidation state, matching our electron energy loss spectroscopy results (Figure S12) and published experimental data on bulk Fe x TaS 2 . We note that without annealing these chemically intercalated materials, we observe neither superlattice spots in NBED data nor significant changes to the Raman spectra (Figure S5).…”
Section: Resultssupporting
confidence: 88%
“…We find that all Raman spectra in Figure 1e−g display a red shift in the A 1g mode by 8−10 cm −1 from the expected value for 2H-TaS 2 . 34,35 This shift is consistent with electron transfer from Fe to the host lattice, 36,37 in agreement with our DFT calculations. For all calculated structures and magnetic configurations, we found that Fe converges to a +2 oxidation state, matching our electron energy loss spectroscopy results (Figure S12) and published experimental data on bulk Fe x TaS 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardanol is the main component of renewable resources from cardanol shell liquid, and there are rigid benzene ring and flexible C15 unsaturated chain in its structure, 18,19 which was used to preparation of cardanol‐based softener, surfactant, diluent 20–26 . Cardanol was utilized to fabricate UV‐curable resins, which endow UV‐curing resin with good flexibility, hydrophobicity, heat resistance, and other excellent properties 27–31 .…”
Section: Introductionmentioning
confidence: 99%